Pembibitan Mangrove Bersama Pokmaswas Bina Lestari untuk Menjaga Ekosistem Pesisir Lembung, Galis, Pamekasan - Akhmad Farid; Meria Zakiyah Alfisuma; Aulia Fitriyana; Anggi Tria Puspitasari; Gilang Romadhon (Yayasan Literasi Sains Indonesia, 2026)
The “Green Movement: Mangrove Nursery with Pokmaswas Bina Lestari” program in Lembung Village, Galis Sub District, Pamekasan District aims to strengthen the capacity of coastal communities in mangrove nursery management and strengthening the role of Pokmaswas as a key actor in community-based conservation. Implemented through a participatory-collaborative approach, this activity actively involved the local community in each stage of the process, from propagule collection and preparation of seeding media to periodic monitoring and maintenance. The program successfully produced approximately 5,000 Rhizophora stylosa seedlings, achieving a 99% survival rate after two months. This high rate reflects not only the suitability of local environmental conditions but also the effectiveness of community engagement and shared responsibility in protecting coastal ecosystems. In addition to ecological contributions such as shoreline stabilization and habitat enhancement, this initiative also generated social and economic benefits. Community awareness of environmental stewardship increased significantly, and new opportunities emerged, including educational tourism, environmental outreach, and potential income from mangrove seedling sales. Overall, the program demonstrates how collaborative conservation efforts can deliver sustainable environmental impacts while empowering coastal communities.